(untitled) (Economic and Political Thought, 2017)
The research problem: determination of the impact of investment in 2007 and 2014 on the level of GDP growth in particular macro-regions in Poland in the long term. The main issue raised in the article is to define the investment processes at a macro as well as a micro level from the perspective of companies in six Polish macro-regions. Investment in selected European countries, especially in Poland, in contrast to the United States, remains significantly below the pre-crisis level. The decrease in investment spread out to all sectors of the market, among others: companies, public sector, and also households. The aim of the article is to examine the importance of investment in 2007 and 2014 in individual macro-regions in Poland, especially at the level of investment in fixed assets identified by modern economy, i.e. machinery, equipment, means of transport, housing, other buildings and structures, IT-telecommunications equipment and solutions or intellectual property. Uncertainty of the future characterizes Europe, especially in the face of the strong inflow of migrants, against which Europe does not know how to defend. The research hypothesis: the condition necessary for the increase in the competitiveness of the Polish economy in macro-regions, as well as throughout the European Union, is the need to increase the investment with particular focus on those sectors that have the highest added value and economic viability, and may become international, which will be conducive to the competitiveness of the economy. The research method: review of statistical data, offering hypotheses and an attempt to verify them with the use of methods that are commonly used in science. Expected results: faster economic growth of Poland in comparison to European countries.